2014
DOI: 10.5348/ijcri-2014-03-478-cr-9
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged aphasia and perfusion computed tomography abnormalities in migraine with aura

Abstract: International Journal of Case Reports and Images (IJCRI) is an international, peer reviewed, monthly, open access, online journal, publishing high-quality, articles in all areas of basic medical sciences and clinical specialties.Aim of IJCRI is to encourage the publication of new information by providing a platform for reporting of unique, unusual and rare cases which enhance understanding of disease process, its diagnosis, management and clinico-pathologic correlations. Migraine with aura is defined as a recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…In our case, CT perfusion, performed during progressive neurological symptoms was consistent with a migraine during the aura phase rather than a cerebral infarct, because it showed perfusion changes with hypoperfusion (increased mean transit time) in the left hemisphere (not restricted to any one vascular territory) without significant cerebral blood volume changes. These findings were consistent with the literature data concerning perfusion patterns on CT perfusion[56] but also on MRI perfusion[7] during a migraine with aura attack.…”
Section: Discussionsupporting
confidence: 93%
“…In our case, CT perfusion, performed during progressive neurological symptoms was consistent with a migraine during the aura phase rather than a cerebral infarct, because it showed perfusion changes with hypoperfusion (increased mean transit time) in the left hemisphere (not restricted to any one vascular territory) without significant cerebral blood volume changes. These findings were consistent with the literature data concerning perfusion patterns on CT perfusion[56] but also on MRI perfusion[7] during a migraine with aura attack.…”
Section: Discussionsupporting
confidence: 93%
“…An accurate ophthalmological evaluation, including best-corrected visual acuity, slit-lamp biomicroscopy, intraocular pressure measurement, and indirect ophthalmoscopy, by excluding optical media, retinal, or optic nerve diseases, can help in the differential diagnosis. It has recently been observed that perfusion CT imaging can help in the decision-making process leading to the differential diagnosis of symptoms mimicking a stroke and, therefore, can direct to appropriate treatment (Nieuwkamp et al, 2010 ; Hansen et al, 2011 ; Miller and Goldberg, 2012 ; Campbell et al, 2013 ; Shah et al, 2013 ; Angermaier et al, 2014 ; Rath et al, 2017 ; Ridolfi et al, 2018 ; Granato et al, 2020 ). Diagnostic accuracy can be further improved by refining the diagnostic criteria of transient ischemic attacks, which can help to separate them from mimics (Lebedeva et al, 2018 ; Dolmans et al, 2019 ).…”
Section: Migraine Comorbidity As Judged By Neuroimaging Techniquesmentioning
confidence: 99%
“…13 A limited number of case reports as well as a short series of patients with MA have reported, in some cases, an abnormal PCT pattern. [14][15][16][17][18][19][20][21] The aim of the current study was to determine the clinical characteristics of MA as well as the frequency and patterns of PCT alterations, in a series of patients with MA mimicking acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…The depolarization wave causes vasodilation and an increase in regional cerebral blood flow (CBF), which has been termed spreading hyperemia, followed by a prolonged period of hypoperfusion lasting 1–2 h, called spreading oligemia 13 . A limited number of case reports as well as a short series of patients with MA have reported, in some cases, an abnormal PCT pattern 14‐21 …”
Section: Introductionmentioning
confidence: 99%